Overreporting and Investigation in the New York City Child Welfare System: A Child’s Perspective - Daniella Rohr; Melissa Friedman (Columbia Journal of Race and Law, 2025)
Child welfare agencies are tasked with protecting children, and in so doing, with investigating allegations of abuse and neglect. If done properly, such investigations can promote child safety. But the data suggests that New York City’s Administration for Children’s Services (“ACS”) subjects far more children and families to intrusive investigations than is necessary. Nearly 100,000 children in New York City are investigated by the ACS each year, and ACS only seeks entry or body-search warrants in 0.4% of investigations. Moreover, the vast majority of these investigations are executed in homes where ACS ultimately decides that it is unlikely any abuse or neglect occurred. Such investigations come at a high cost to children: they are aggressive, traumatic, and coercive.